Modulating Hippocampal Plasticity with In Vivo Brain Stimulation - Rohan, Joyce G. (J Neurosci, 2015)
Investigations into the use of transcranial direct current stimulation (tDCS) in relieving symptoms of neurological disorders and enhancing cognitive or motor performance have exhibited promising results. However, the mechanisms by which tDCS effects brain function remain under scrutiny. We have demonstrated that in vivo tDCS in rats produced a lasting effect on hippocampal synaptic plasticity, as measured using extracellular recordings. Ex vivo preparations of hippocampal slices from rats that have been subjected to tDCS of 0.10 or 0.25 mA for 30 min followed by 30 min of recovery time displayed a robust twofold enhancement in long-term potentiation (LTP) induction accompanied by a 30% increase in paired-pulse facilitation (PPF). The magnitude of the LTP effect was greater with 0.25 mA compared with 0.10 mA stimulations, suggesting a dose-dependent relationship between tDCS intensity and its effect on synaptic plasticity. To test the persistence of these observed effects, animals were stimulated in vivo for 30 min at 0.25 mA and then allowed to return to their home cage for 24 h. Observation of the enhanced LTP induction, but not the enhanced PPF, continued 24 h after completion of 0.25 mA of tDCS. Addition of the NMDA blocker AP-5 abolished LTP in both control and stimulated rats but maintained the PPF enhancement in stimulated rats. The observation of enhanced LTP and PPF after tDCS demonstrates that non-invasive electrical stimulation is capable of modifying synaptic plasticity. SIGNIFICANCE STATEMENT Researchers have used brain stimulation such as transcranial direct current stimulation on human subjects to alleviate symptoms of neurological disorders and enhance their performance. Here, using rats, we have investigated the potential mechanisms of how in vivo brain stimulation can produce such effect. We recorded directly on viable brain slices from rats after brain stimulation to detect lasting changes in pattern of neuronal activity. Our results showed that 30 min of brain stimulation in rats induced a robust enhancement in synaptic plasticity, a neuronal process critical for learning and memory. Understanding such molecular effects will lead to a better understanding of the mechanisms by which brain stimulation produces its effects on cognition and performance.